2007
DOI: 10.1111/j.1460-9592.2007.02380.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol–ketamine vs propofol–fentanyl combinations for deep sedation and analgesia in pediatric patients undergoing burn dressing changesa

Abstract: Both propofol-ketamine and propofol-fentanyl combinations provided effective sedation and analgesia during dressing changes in pediatric burn patients. But propofol-ketamine combination was superior to propofol-fentanyl combination because of more restlessness in patients given propofol-fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 17 publications
3
48
0
5
Order By: Relevance
“…Several investigators, in various studies which were done, found that the co administration of ketamine with propofol during induction prevented the adverse haemodynamic outcomes which were seen when propofol was used alone [5,6]. Several strategies, including IV administration of 0.5 mg/kg ketamine prior to propofol induction and infusion, have been shown to decrease adverse haemodynamic events which were associated with isolated use of propofol [5].…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators, in various studies which were done, found that the co administration of ketamine with propofol during induction prevented the adverse haemodynamic outcomes which were seen when propofol was used alone [5,6]. Several strategies, including IV administration of 0.5 mg/kg ketamine prior to propofol induction and infusion, have been shown to decrease adverse haemodynamic events which were associated with isolated use of propofol [5].…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained from other studies. 5,9,10,15 CONCLUSION Following Conclusions are drawn from the Present Study- Both ketamine and fentanyl in propofol infusion for short surgical procedures are equally safe and efficacious.  Infusion of propofol-ketamine and propofol-fentanyl both provides stable haemodynamics and good recovery profile.…”
Section: Discussionmentioning
confidence: 72%
“…Similar results were obtained from other studies. 1,5,8,9,10,12,13 Vallejo M. C. et al 5 also observed no statistical significance in their study. Similar results were obtained from other studies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As an advantage, it maintains the airway refl exes, blood pressure, and heart rate by indirect release of norepinephrine. The occurrence of hallucinations, a signifi cant adverse effect, may be attenuated by concomitant administration of benzodiazepines or propofol 37,38 . In a meta-analysis of ketamine at low doses and postoperative consumption of opioids, the authors concluded that there is a reduction of up to one-third in total dose administered.…”
Section: Ketaminementioning
confidence: 99%